PROGNOSTIC VARIABLES IN SCHIZOPHRENIA* - Kulhara, P. (Medknow Publications, 1989)
This study examined the relationship between measures of outcome and socio-demographic arid diagnostic variables in schizophrenia. Product moment co-efficient of correlation and stepwise multiple regression were the main statistical techniques of analyses. The results of the study indicate that DSM-III diagnosis of schizophrenia, duration of illness, and Present State Examination-PSE Syndrome of non-specific psychosis are important predictors of outcome. CATEGO and Research Diagnostic Criteria-RDC diagnosis of Schizophrenia, and Schneiderian First Rank Symptoms were found to be poor predictors of outcome. Socio-demographic and clinical variables like gender of the patient, place of origin, impersistence at work, poor premorbid work record, hospitalization at the time of admittance into the study, loss of interest, affective flattening and incoherent speech were found to have prognostic implications.